Pediatric Inflammatory Multisystem Syndrome: Statement by the Pediatric Section of the European Society for Emergency Medicine and European Academy of Pediatrics - Nijman, Ruud G.; De Guchtenaere, Ann; Koletzko, Berthold; Ross Russell, Rob; Copley, Sian; Titomanlio, Luigi; del Torso, Stefano; Hadjipanayis, Adamos (Frontiers in Pediatrics, 2020)
A rise in cases with a new hyperinflammatory disease in children has been reported in Europe and in the Unites States of America, named the Pediatric Inflammatory Multisystem Syndrome—temporally associated with SARS-CoV-2 (PIMS-TS). There appears to be a wide spectrum of signs and symptoms with varying degrees of severity, including a toxic shock like presentation with hypovolaemia and shock, and a Kawasaki-like presentation with involvement of the coronary arteries. Most of these children have evidence of a previous infection with SARS-CoV-2, or a history of significant exposure, but not all. Limited data exist on the incidence of PIMS-TS, but it remains a rare condition. Early recognition and escalation of care is important to prevent the development of serious sequelae, such as coronary artery aneurysms. Clinicians assessing febrile children in primary and secondary care should include PIMS-TS in their differential diagnoses. In children fulfilling the case definition, additional investigations should be undertaken to look for evidence of inflammation and multiorgan involvement. Suspected cases should be discussed with experts in pediatric infectious diseases at an early stage, and advice should be sought from critical care in more severe cases early. There is limited consensus on treatment; but most children have been treated with immunoglobulins or steroids, and with early consideration of biologicals such anti-TNF and anti-IL1 agents. Treatment should ideally be within the context of controlled treatment trials. Clinicians are encouraged to document and share their cases using research registries.